2003
DOI: 10.1093/qjmed/hcg059
|View full text |Cite
|
Sign up to set email alerts
|

Admission diagnosis of cerebral malaria in adults in an endemic area of Tanzania: implications and clinical description

Abstract: Cerebral malaria was grossly overdiagnosed, resulting in unnecessary treatment and insufficient investigation of other possible diagnoses, which could lead to higher mortality. Extension of this misperception to the assessment of cause of death in community surveys may lead to an overestimation of the impact of malaria in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 22 publications
0
85
0
1
Order By: Relevance
“…34,35 In a randomized trial, insecticide-impregnated nets did not reduce mortality in Ghanaian adults, suggesting that malaria is not a major cause of death in this age group. 36 However, immunologically naive adult visitors to endemic areas are highly susceptible and major epidemics with high case fatality may occur in areas of initially low transmission to which malaria returns after having been nearly eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 In a randomized trial, insecticide-impregnated nets did not reduce mortality in Ghanaian adults, suggesting that malaria is not a major cause of death in this age group. 36 However, immunologically naive adult visitors to endemic areas are highly susceptible and major epidemics with high case fatality may occur in areas of initially low transmission to which malaria returns after having been nearly eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial, cryptococcal, and tuberculous meningitis and viral encephalitis commonly occur in PNG children in this situation (3,26,27). In addition, African studies reveal that approximately one-quarter of children diagnosed with cerebral malaria have such alternative diagnoses (45), and the proportion of adults with such alternative diagnoses appears to be substantially higher (29). Although artemether may improve the outcome from sepsis in the absence of malaria (35), our predictive modeling suggests that repeated recommended daily doses of intramuscular artemether will, in the presence of meningeal inflammation, result in accumulation to levels approaching and in some cases exceeding those resulting in significant neuronal toxicity and death in vitro (Ͼ100 g/liter) (46).…”
Section: Discussionmentioning
confidence: 99%
“…In several recent studies, the routine slide reading for malaria was shown to have very poor positive predictive value when compared to expert microscopy [39,40]. In one centre, only 13% of adults with diagnosis of cerebral malaria actually had parasitemia on their blood film [41]. These data suggests that over-diagnosis of clinical malaria may be widespread in India and therefore may lead to under-treatment of other life threatening conditions.…”
Section: Burden Of Neonatal Malariamentioning
confidence: 99%